Peran Kendali Glukosa terhadap Indeks Massa Tubuh dan Lingkar Lengan Atas pada Pasien Diabetes Mellitus Tipe 2 di Malang Raya - Sukosari Devantari; Silvy Amalia Falyani; Rahma Triliana (Jurnal Kedokteran Komunitas, 2020)
Background: Diabetes Mellitus (DM) is a degenerative disease caused by impaired insulin function, marked by hyperglycemia. Chronic hyperglycemia may decrease the nutritional status of DM patients by measuring Body Mass ndex (BMI) and Upper Arm Circumference (UAC). This study aimed to look at the role of glucose control in BMI and UAC in Type 2 DM patients.Methods: This reserach was cross sectional studies. The respondents are male and female of diabetic patients without complications over the age of 40 years. The subjects were divided into the controlled group and uncontrolled group. Each group performed weight measurements with weight scale, body height with microtoise and UAC with a measuring tape. Independent T-Test was used to analyze the data , followed by a Pearson correlation test with a significance level of p<0.05.Results: There was no significant difference between glucose control, BMI (p=0.921), right UAC (p=0.611) and left UAC (p=0.406) in controlled group and uncontrolled group. Glucose control had no correlation to BMI (r=-0.061). There was also no correlation between glucose control, right UAC (r=0.161) and left UAC (r=0.197).Conclusion: Glucose control had no role in body mass index and upper arm circumference towards patients with diabetes mellitus type 2 in Malang.Keywords: Glucose control, body mass index, upper arm circumference, type 2 diabetes mellitus